Visualisasi Lagu Anak “Angka Seperti Apa” - Harwana, Typanni; Uttara, Sabeth (BHAGIRUPA, 2022)
The lack of visualization of the "what number" song causes children to be less interested in learning. The visualization of the song "what kind of number" contains only audio and text elements, making it difficult for children to understand. One aspect of childhood learning is the cognitive, and one is knowing Numbers. In knowing Numbers a child will learn the concepts of Numbers in a concrete way, using the concept of numerical recognition, a child will learn the names of Numbers that enable it to see and pronounce a number and can enhance its ability to detect both its forms and its pronunciation gradually. Visualization of children's songs is needed to attract children's attention in learning and develop children's cognitive abilities. Then a combination of audio and visual media - audio-visual media is needed.